G-Sense: a graphical interface for SENSE simulator - Rosa, Pedro M. P. (2011)
“Copyright © [2009] IEEE. Reprinted from First International Conference on Advances in System Simulation.ISBN:978-1-4244-4863-0. This material is posted here with permission of the IEEE. Internal or personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution must be obtained from the IEEE by writing to pubs-permissions@ieee.org. By choosing to view this document, you agree to all provisions of the copyright laws protecting it.”